Penerapan Metode Bercerita Untuk Meningkatkan Daya Serap Anak Usia 9-11 Tahun Di Rayon II Gmit Ebenhaezer Hombol Klasis Teluk Kabola - Delila Tanaem; Adolfina Oualeng; Christiana A. Ouw (Peneliti.net, 2022)
The problems formulated in this study are how to apply the storytelling method in learning for children aged 9-11 years in rayon II GMIT Ebenhaezer Hombol Klasis Teluk Kabola and how to increase children's absorption by using the storytelling method for middle-class children aged 9-11 years in rayon II GMIT Ebenhaezer. Kabola Bay Classic Symbol. The purpose of the study was to determine the application of the storytelling method in increasing the absorption of children aged 9-11 years at Rayon II GMIT Ebenhaezer Hombol Klasis Kabola Bay and to determine the absorption of children's Bible stories told by the teacher. The object of research is 20 children. The type used is classroom action research. The results showed that the application of the storytelling method to increase children's absorption in the learning process in Rayon II of the GMIT Ebenhaezer Hombol Klasis Teluk Kabola congregation proved that children could absorb the stories conveyed by the teacher in the learning of children and adolescents. The conclusion in this study is that the teacher's ability is inadequate and creative so that it affects the absorption of children. The teacher only uses the impromptu lecture method so that the children are bored and bored with the method. The suggestion given by the author is that being a teacher must be creative, innovative and have the skills to teach and be able to create a harmonious atmosphere for children.